Dimensi Fikih Moderat dalam Putusan Hakim atas Perceraian yang Disebabkan Penyalahgunaan Aplikasi Karaoke Online - Diana Wati, Erlin; Muhammad Wahib; Faisal; Abdul Aziz Harahap (State of Islamic Institute Langsa, 2023)
This study is oriented in identifying the dimensions of moderate jurisprudence values in the judge's decision on divorce caused by the misuse of online karaoke applications in case number 400/Pdt.G/2021/PA. Jpr at the Jayapura Religious Court. This article is classified as literature research with a qualitative approach. The methodology used is the study of normative-empirical law related to the theory of moderate jurisprudence initiated by Quraish Shihab. The results of the study concluded that moderate and comprehensive legal considerations related to polemics on marriage cases caused by digital developments were reviewed from several factors, including; First, the value of fiqh al-maqasid. In the basis of divorce law rulings which refer to the difficulty of the potential realization of marriages that are sakinah, mawaddah, wa rahmah. Second, the value of fiqh al-awlawiyat in the basis of divorce law rulings which emphasizes the consideration of priority scales to avoid damage rather than attracting benefits when the marriage is maintained. Third, the value of fiqh al-muwazanat in the basis of divorce law decisions that emphasize greater benefit by choosing the path of divorce. Fourth, the value of fiqh al-maa'lat in the basis of legal rulings that can have social implications for the realization of the benefits of married life in the digital era